Alguns aspectos do comportamento de cepas silvestres de Trypanosoma cruzi em camundongos e Calomys callosus (Rodentia) Some aspects of the behavior of wild strains of Trypanosoma cruzi in mice and Calomys callosus (Rodentia) - Dalva A. Mello; Edna Valin; Maria Lúcia Teixeira (Revista de Saúde Pública, 1979)
Foram estudadas quatro cepas silvestres de T. cruzi: M226 isolada de Calomys callosus (Rodentia) e R52, R64 e R65 isoladas de Didelphis albiventris (Marsupialia). Estes animais foram coletados no município de Formosa, Goiás, Brasil. Os aspectos abordados, relacionados com o comportamento destas cepas em camundongos "swiss" 40 e C. callosus nascidos em laboratório, foram: parasitemia, prepatência, letalidade e histopatologia. Os resultados indicaram que as quatro cepas tinham baixa virulência para os animais testados. A parasitemia sempre se apresentou baixa e regular para os C. callosus. Nos camundongos, só raramente a parasitemia era patente. A prepatência nos C. callosus variou em média entre 9,2 a 10,2 dias, enquanto nos camundongos ficou entre 12-48 dias. A letalidade para C. callosus foi 7,7% e para camundongos 12,0%. Os estudos histopatológicos mostraram que somente 17,2% dos C. callosus apresentaram parasitismo tissular, enquanto em 25% dos camundongos foram encontrados pseudocistos íntegros ou rompidos. Houve um nítido miotropismo das quatro cepas tanto nos camundongos quanto nos C. callosus. Four wild strains of T. cruzi were studied for this paper: M226 isolated from Calomys callosus (Rodentia) and R52, R64, and R65 from Didelphis albiventris (Marsupialia). The animals were captured in the county of Formosa in the State of Goias. trypanosome strains were studied in 40 Swiss mice and in laboratory stock of C. callosus. The following aspects were focused: parasitemia, prepatent period, lethality, and histopathologic reactions. Results indicated that these strains have low virulence for inoculated animals. Parasitemia was always low and regular for C. callosus. In mice, however, parasites were seen only in a few instances in the peripheral blood. The prepatent periods were 9.2 to 10.2 days for C. callosus and 12 to 48 days for mice. Lethality was 7.7% for C. callosus and 12% for mice. The parasites were found in the tissues of the inoculated animals in the proportions of 17.2% for C. callosus and 25% for mice. Tissue reaction in both rodent species showed that all the T. cruzi strains had strong affinity for skeletal or cardiac muscle.